Cultural Transmission, Evolution, and Revolution in Vocal Displays: Insights From Bird and Whale Song - Garland, Ellen C.; McGregor, Peter K. (Frontiers in Psychology, 2020)
Culture, defined as shared behavior or information within a community acquired through some form of social learning from conspecifics, is now suggested to act as a second inheritance system. Cultural processes are important in a wide variety of vertebrate species. Birdsong provides a classic example of cultural processes: cultural transmission, where changes in a shared song are learned from surrounding conspecifics, and cultural evolution, where the patterns of songs change through time. This form of cultural transmission of information has features that are different in speed and form from genetic transmission. More recently, culture, vocal traditions and an extreme form of song evolution has been documented in cetaceans. Humpback whale song ‘revolutions’, where the single population-wide shared song type is rapidly replaced by a new, novel song type introduced from a neighbouring population, represents an extraordinary example of ocean basin-wide cultural transmission rivalled in its geographic extent only by humans. In this review, we examine the cultural evolutions and revolutions present in some birdsong and whale song, respectively. By taking a comparative approach to these cultural processes, we review the existing evidence to understand the similarities and differences for their patterns of expression and the underlying drivers, including anthropogenic influences, which may shape them. Finally, we encourage future studies to explore the role of innovation vs. production errors in song evolution, the fitness information present in song, and how human-induced changes in population sizes, trajectories and migratory connections facilitating cultural transmission may be driving song revolutions.